PEMBERDAYAAN SOSIAL WANITA NELAYAN TERDAMPAK COVID-19 MELALUI USAHA IKAN ASIN DI KAWASAN PESISIR KOTA BENGKULU - Herlina, Muria; Jayaputra, Novi Hendrika (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2021)
Social empowerment activities aim to make fishermen families able to meet their basic needs. Due to the impact of covid-19, their income decreases and cannot fulfill their basic needs. The location is in Neighbourhood Number X of Sumber Jaya Village in the coastal area of ​​Bengkulu City. The method was started from socialization, mapping and social approach. It was agreed that making salted fish is the solution, because fishermen are used to collecting wages to weed fish. The implementation starts from August to the end of October 2020. The practice starting from the procurement of equipment for making salted fish, raw materials, making fish dryer and assisting in making salted fish according to the manufacturing flow. From 300 kg of wet fish (6 types of fish), resulting in 276 kg of salted fish. The price of wet fish is Rp. 3000, - / kg, and the price of salted fish is Rp. 17,000 to Rp. 20,000 / kg, while the wage for weeding fish is Rp. 3000, - / kg. Fixed income per week of Rp. 575,000 to Rp. 630,000 / person, above the Regional Minimum Wage of Bengkulu City in 2020.